2014
DOI: 10.1063/1.4875516
|View full text |Cite
|
Sign up to set email alerts
|

A unified model for simulating liquid and gas phase, intermolecular energy transfer: N2 + C6F6 collisions

Abstract: Molecular dynamics simulations were used to study relaxation of a vibrationally excited C6F6* molecule in a N2 bath. Ab initio calculations were performed to develop N2-N2 and N2-C6F6 intermolecular potentials for the simulations. Energy transfer from "hot" C6F6 is studied versus the bath density (pressure) and number of bath molecules. For the large bath limit, there is no heating of the bath. As C6F6* is relaxed, the average energy of C6F6* is determined versus time, i.e., ⟨E(t)⟩, and for each bath density ⟨… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
199
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(216 citation statements)
references
References 105 publications
(132 reference statements)
17
199
0
Order By: Relevance
“…33 In the inset of Figure 8 the results of the simulations described above for classical microcanonical, classical microcanonical + ZPE, and quantum microcanonical sampling are presented. The classical microcanonical sampling result was presented previously, 26 and its initial ⟨E⟩ is smaller since it does (2) a The vibrational frequencies are in cm −1 . For "model C 6 H 6 " the masses of the F-atoms are changed to that for the H-atom without changing any of the other potential parameters.…”
Section: In Ref 26) As a Results And Shown Inmentioning
confidence: 99%
See 4 more Smart Citations
“…33 In the inset of Figure 8 the results of the simulations described above for classical microcanonical, classical microcanonical + ZPE, and quantum microcanonical sampling are presented. The classical microcanonical sampling result was presented previously, 26 and its initial ⟨E⟩ is smaller since it does (2) a The vibrational frequencies are in cm −1 . For "model C 6 H 6 " the masses of the F-atoms are changed to that for the H-atom without changing any of the other potential parameters.…”
Section: In Ref 26) As a Results And Shown Inmentioning
confidence: 99%
“…In the low-pressure, single collision limit for C 6 F 6 + N 2 energy transfer, the proportionality constants C 1 and C 2 for k 1 and k 2 , i.e.. k = C × ρ, become independent of density ρ. The previous study 26 indicated that a 40 kg/m 3 N 2 bath density well approximates the single collision limit for the C 6 F 6 −N 2 system since the C 1 and C 2 parameters were very similar for the 40 and 80 kg/m 3 N 2 bath densities. For the work reported here, an additional simulation was performed for a lower N 2 bath density of 20 kg/m 3 to ensure the single collision convergence of the previous 40 kg/m 3 simulation.…”
Section: Energy Transfer Dynamicsmentioning
confidence: 88%
See 3 more Smart Citations